Sedentary Behaviour and Diabetes Information as a Source of Motivation to Reduce Daily Sitting Time in Office Workers: A Pilot Randomised Controlled Trial. Issue 2 (24th January 2020) - Rollo, Scott; Prapavessis, Harry
Abstract : Background: Using the motivational phase of the Health Action Process Approach (HAPA), this study examined whether sedentary behaviour and diabetes information is a meaningful source of motivation to reduce daily sitting time among preintending office workers. Methods: Participants ( N = 218) were randomised into HAPA‐intervention (sedentary behaviour), HAPA‐attention control (physical activity), or control (no treatment) conditions. Following treatment, purpose‐built sedentary‐related HAPA motivational constructs (risk perception, outcome expectancies, self‐efficacy) and goal intentions were assessed. Only participants who had given little thought to how much time they spent sitting (preintenders) were used in subsequent analyses (n = 96). Results: Significant main effects favouring the intervention group were reported for goal intentions: to increase number and length of daily breaks from sitting at work; to reduce daily sitting time outside of work; to increase daily time spent standing outside of work, as well as for outcome expectancies ( p values ≤ .05; ɳp 2 values ≥.08). Only self‐efficacy ( β range = 0.39–0.50) made significant and unique contributions to work and leisure‐time‐related goal intentions, explaining 11–21 per cent of the response variance. Conclusions: A brief, HAPA‐based online intervention providing information regarding sedentary behaviour and diabetes risk may be an effective source of motivation.